Phenolic Extraction of Moringa Oleifera Leaves Induces Caspase-Dependent and Caspase-Independent Apoptosis through the Generation of Reactive Oxygen Species and the Activation of Intrinsic Mitochondrial Pathway in Human Melanoma Cells. (10th March 2021) - Do, Bich Hang; Hoang, Nghia Son; Nguyen, Thi Phuong Thao; Ho, Nguyen Quynh Chi; Le, Thanh Long; Doan, Chinh Chung
Abstract: Moringa oleifera Lam. has long been used to treat many diseases, including diabetes, aging, inflammatory, and cancer. Many studies have revealed that the crude extract of Moringa oleifera Lam. leaves possesses anticancer property. Therefore, in this study, the extract of Moringa oleifera leaves was fractionated using different solvents to figure out the most effective fraction for anti-proliferative effect on melanoma cells. Methanol extract (MO-ME), hexane fraction (MO-HE), chloroform fraction (MO-CH), ethyl acetate fraction (MO-EA), and water-soluble fraction (MO-WA) of Moringa oleifera leaves were prepared. Total phenolic and flavonoid contents were determined. The anti-proliferative activity on melanoma cells and normal cells was investigated using WST-1 assay. The apoptotic activity was assessed by testing DNA condensation, DNA fragmentation, and phosphatidylserine (PS) externalization. The expression of apoptosis-related genes, the mitochondrial depolarization, and reactive oxygen species (ROS) were then examined to clarify the underlying molecular mechanisms. In this regard, MO-ME, MO-EA, and MO-CH inhibited the proliferation of both A375 human melanoma cells and A2058 human melanoma cells, but had little effect on WS1 normal human skin fibroblasts and primary normal human dermal fibroblasts (NHDF). Among fractions, the phenolic-rich MO-EA markedly inhibited the growth of A375 cells in a dose- and time-dependent manner. The anti-proliferation was supposed to be mediated via apoptosis, which was demonstrated by the significant increase of condensed chromatin, DNA fragmentation, and PS externalization. The apoptosis was stimulated by enhanced ROS production and reduction of mitochondrial membrane potential. MO-EA activated Bax while reducing Bcl-2 expression, leading to an increase in Bax/Bcl-2 ratio. The mechanisms of cell death involved in activation of Caspase-3/7 and Caspase-9 (Caspase-dependent pathway), activation, and translocation of apoptosis-inducing factor (AIF) into the nucleus (Caspase-independent pathway). Our study indicated that the phenolic-rich fraction exerted significant anticancer effects on melanoma cells in vitro which involved in Caspase-dependent and Caspase-independent apoptosis pathways mediated by mitochondrial ROS. These results provided a fundament for the using of phenolic-rich fraction of Moringa oleifera leaves to treat skin cancer effectively.